Inflammatory and Procoagulant Mediator Interactions in an Experimental Baboon Model of Venous Thrombosis - Wakefield, Thomas W; Greenfield, Lazar J; Rolfe, Mark W; DeLucia, Alphonse, III; Strieter, Robert M; Abrams, Gerald D; Kunkel, Steven L; Esmon, Charles T; Wrobleski, Shirley K; Kadell, Amy M; Burdick, Marie D; Taylor, Fletcher B (Thrombosis and Haemostasis, 1993)
Theoretic and in vitro evidence suggests that thrombosis and inflammation are interrelated. The purpose of the present study was to define the relationship between inflammation and deep venous thrombosis (DVT) in an in vivo model. Initiation of DVT was accomplished by administration of antibody to protein C (HPC4, 2 mg/kg) and tumor necrosis factor (TNF, 150 μg/kg); stasis; and subtle venous catheter injury. Thrombosis was assessed by thrombin-antithrombin assay (TAT), 125I-fibrinogen scanning (scan) over both the proximal and distal iliac veins, and ascending venography. Cytokines TNF, interleukin-6 (IL-6), monocyte chemotactic protein-1 (MCP-1), and interleukin-8 (IL-8) were measured along with differential white blood cell counts, platelet counts, fibrinogen (FIB), and erythrocyte sedimentation rates (ESR). Baboon pairs were sacrificed on day 3 (T + 3d), T + 6d, and T + 9d and veins removed. All animals developed inferior vena cava and left iliofemoral DVT by venography; no right DVT was found. TAT was elevated by T + 1hr and peaked at T + 3hrs. Left iliofemoral DVT was found at T + 1hr by scan and reached a 20% uptake difference between the affected left and nonaffected right side at T + 3hrs. TNF peaked at T + 1hr; MCP-1 peaked at T + 6hrs; IL-8 and IL-6 peaked on T + 2d; all cytokines declined to baseline. TNF and TAT elevations were found to correlate with all cytokines; elevations in IL-8 were correlated with elevations in MCP-1 and IL-6 (p <0.05). Correlation between cytokines and scan revealed a significant (p <0.05) relationship only between elevations in IL-6 and distal iliac fibrin accumulation; no significant correlation was found between IL-8 and MCP-1 and scan. Increased mature polymorphonuclear leukocytes were found by T + 2d; immature forms were prominent at T + 3hrs, T + 6hrs, and T + 2d. Increased monocytes were noted by T + 4d; increased lymphocytes and platelets by T + 8d. ESR and FIB were elevated by T + 3d. Histopathologic study revealed venous inflammation at T + 3d, with beginning thrombus organization by T + 6d. MCP-1 localized to areas of thrombus and phlebitis. The development of DVT in this model involves inflammatory as well as coagulant activity. We conclude that this model allows studies on the role of inflammatory mediators in the development and natural history of DVT.